Hospitalization as an opportunity to correct errors in anticoagulant treatment in patients with atrial fibrillation. Issue 12 (16th December 2019) - Angel, Yoel; Zeltser, David; Berliner, Shlomo; Ingbir, Merav; Shapira, Itzhak; Shenhar‐Tsarfaty, Shani; Rogowski, Ori
Abstract : Aims: To assess whether hospitalization may assist in correcting errors in anticoagulant therapy among patients with atrial fibrillation (AF). Methods: Our cohort included patients admitted to our institution with a history of AF between 2016 and 2018. We categorized patient's treatment upon admission and discharge as lacking (no treatment despite indication), inadequate (according to individual characteristics) or adequate . We assessed adequacy of treatment upon discharge and determined factors associated with correcting admission errors. Results: Of 4427 patients admitted with a history of AF, the categorization to lacking, inadequate and adequate treatment was 1746 (39.4%), 1237 (27.9%) and 1444 (32.6%) patients, respectively. Of those with inadequate treatment, the most common types of errors were direct oral anticoagulant (DOAC) underdosing ( n = 578; 46.7%), vitamin‐K antagonists when DOAC was indicated ( n = 258; 20.9%), DOAC despite contraindication to DOAC ( n = 166; 13.4%) and DOAC overdosing ( n = 124; 10%). Upon discharge 688 (18.6%, out of n = 3694) corrections but also 316 (8.6%) new mistakes were found. On multivariate logistic regression, the factors associated with correction of an error on admission were hospitalization due to AF (odds ratio [OR] 2.94 [2.39–3.61]), hospitalization in the neurologic or geriatric wards (OR 2.79 [2.04–3.80]), female sex (OR 1.34 [1.10–1.63]) and a history of stroke (OR 1.47 [1.17–1.86]), while the presence of a contraindication to DOAC decreased the chance of correction (OR 0.10 [0.06–0.18]). Conclusion: Hospitalization for any reason may contribute to correction of errors in AC treatment in patients with AF. Unfortunately, a significant portion of patients remains inadequately treated by both outpatient and inpatient providers.